2019
DOI: 10.1111/jcmm.14362
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LncRNA SCAMP1 suppressed malignant biological behaviours of glioma cells via modulating miR‐499a‐5p/LMX1A/NLRC5 pathway

Abstract: Dysregulation of long non‐coding RNAs (lncRNAs) confirm that it plays a crucial role in tumourigenesis and malignant progression of glioma. The present study demonstrated that LncRNA secretory carrier membrane protein 1 (SCAMP1) was up‐regulated and functioned as an oncogene in glioma cells. In addition, miR‐499a‐5p was down‐regulated meanwhile exerted tumour‐suppressive function in glioma cells. Subsequently, inhibition of SCAMP1 significantly restrained the cell proliferation, migration and invasion, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Several vital lncRNAs were found in the present NP lncRNA-miRNA-mRNA network, and these lncRNAs have not been reported in NP. For example, lncRNA SCAMP1 played an important role in the regulatory network of this study, and it had been reported in a previous study that it may be associated with malignant biological behavior (40). In addition, lncRNA SCAMP1 discovered in the present study were related to the regulation of cancer (41).…”
Section: Discussionsupporting
confidence: 67%
“…Several vital lncRNAs were found in the present NP lncRNA-miRNA-mRNA network, and these lncRNAs have not been reported in NP. For example, lncRNA SCAMP1 played an important role in the regulatory network of this study, and it had been reported in a previous study that it may be associated with malignant biological behavior (40). In addition, lncRNA SCAMP1 discovered in the present study were related to the regulation of cancer (41).…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have reported that lncRNAs are potential miRNA sponges (33,34). Silencing of the lncRNA SCAMP1 inhibits malignant biological behavior in glioma through the miR-499a-5p/LIM homeobox transcription factor 1 alpha/NLR family CARD domain containing 5 signaling pathway (35). HOX transcript antisense RNA directly inhibited WIF-1 level by regulating the promoter region methylation of its histone H3K27, and then activating the Wnt/β-catenin signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the lncRNA found in this article has not been fully reported in previous studies. It is reported that knockdown of lncRNA SCAMP1 suppressed malignant biological behaviors of glioma cells through regulating the miR-499a-5p/LMX1A/NLRC5 pathway (20). Additionally, SCAMP1 could be bound with miR-137 and accelerate the progression of ovarian cancer (OC) (21).…”
Section: Discussionmentioning
confidence: 99%